Serum amyloid A1 (SAA1) protein in human colostrum. Issue 3 (31st January 2018) - Sack, George H.; Zachara, Natasha; Rosenblum, Nadine; Talbot, C. Conover; Kreimer, Simion; Cole, Robert; McDonald, Thomas L.
Abstract : Proteins of the serum amyloid A (SAA) family have been remarkably conserved in evolution. Their biologic function(s) are not fully defined but they are likely to be a part of primordial host defense. We have detected a ∼ 12‐kDa protein reacting with antibodies against serum amyloid A (SAA) in human colostrum by western blotting. Mass spectrometry identified the reactive species as SAA1, previously identified as a prominent member of the acute‐phase response in serum. Our finding SAA1 in human colostrum contrasts with bovine, caprine and ovine colostrum where a species corresponding to putative SAA3 is uniformly present. SAA1 protein in human colostrum presumably contributes to neonatal protection. Abstract : The prominent human acute‐phase reactant SAA1 protein has been detected in human colostrum, contrasting bovine, caprine and ovine colostrum where SAA3 protein has been found. A single nucleotide insertion in the human SAA3 gene leads to premature termination. Control of SAA1 expression in human mammary epithelium is novel and presumably provides a survival benefit to the newborn.